2005
DOI: 10.1162/0898929054021102
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Brain Systems for Processing Concrete and Abstract Concepts

Abstract: Behavioral and neurophysiological effects of word imageability and concreteness remain a topic of central interest in cognitive neuroscience and could provide essential clues for understanding how the brain processes conceptual knowledge. We examined these effects using event-related functional magnetic resonance imaging while participants identified concrete and abstract words. Relative to nonwords, concrete and abstract words both activated a left-lateralized network of multimodal association areas previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
429
11
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(532 citation statements)
references
References 51 publications
56
429
11
3
Order By: Relevance
“…Indeed, as shown in Supplementary Table S5 and Figure S1, longer RTs were indeed associated with activity in a distributed cortical network consistent with regions observed in previous studies examining the executive aspects of semantic memory use (Badre et al, 2005;Binder et al, 2005;Goldberg et al, 2007;Hoffman et al, 2010;Raposo et al, 2012;Satpute et al, 2014). Critically, the imaging results presented below are statistically independent of these RT effects.…”
Section: Behavioral Resultssupporting
confidence: 86%
“…Indeed, as shown in Supplementary Table S5 and Figure S1, longer RTs were indeed associated with activity in a distributed cortical network consistent with regions observed in previous studies examining the executive aspects of semantic memory use (Badre et al, 2005;Binder et al, 2005;Goldberg et al, 2007;Hoffman et al, 2010;Raposo et al, 2012;Satpute et al, 2014). Critically, the imaging results presented below are statistically independent of these RT effects.…”
Section: Behavioral Resultssupporting
confidence: 86%
“…The resulting ratings, therefore, may reflect different decision criteria at the concrete and abstract ends of the scale, which is consistent with previous observations that the concreteness ratings scale has a bimodal distribution (e.g., Kousta et al, 2011). Imageability ratings are frequently used interchangeably with concreteness ratings (e.g., Binder et al, 2005;Sabsevitz et al, 2005) because of their high correlation and theoretical relationship in dual coding theory. Instructions for imageability ratings repeatedly refer to arousing a "mental image" (Paivio et al, 1968, p. 4), which is likely to lead naïve participants to focus on vision at the expense of other modalities.…”
Section: Introductionsupporting
confidence: 88%
“…A long history of research has examined processing differences between such abstract and concrete concepts. In particular, concreteness effects refer to a behavioral advantage for words that refer to concrete concepts, which are processed more quickly and accurately than abstract concepts in tasks such as lexical decision and word naming (e.g., Binder et al, 2005;James, 1975;Kroll & Merves, 1986;Schwanenflugel, Harnishfeger & Stowe, 1988;Schwanenflugel & Stowe, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported stronger activation in this general region (and surrounding extrastriate cortex) for reading word-like pseudowords compared to words (Binder et al, 2005a;Kronbichler et al, 2004;Mechelli et al, 2003;Price et al, 1996;Xu et al, 2001). It seems very likely that this difference is related to the longer processing time and visual attention required for reading pseudowords, as the same region showed activation correlated with RT during overt word and pseudoword naming (peak at −42, −55, −10) (Binder et al, 2005a) and during a visual lexical decision task (peak at −42, −52, −17) (Binder et al, 2005b) and was activated by covert shifts of visual attention in an experiment using meaningless geometric shapes to cue the spatial location of targets (peak at −45, −69, −6) (Gitelman et al, 1999). Thus, this general region of visual extrastriate cortex appears to be sensitive to task difficulty and attentional modulation.…”
Section: Discussionmentioning
confidence: 99%